SIMPLE AND EFFECTIVE SEISMIC-RETROFIT TECHNIQUES FOR EARTHEN-MASONRY BUILDINGS - Webster, Fred (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This paper describes how ield studies of the seismic behavior and performance of adobe buildings following earthquakes in California, Central and South America, and shake-table tests performed in different countries have contributed to the development of appropriate and minimally intrusive stability-based retroit measures for culturally and historically signiicant adobe structures, and for low-strength masonry, in general. It concludes that understanding how these buildings perform during and after earthquakes is the key to directing minimal, stability-based intervention efforts, aimed at the speciic needs and structural behaviors of unreinforcedadobe buildings without compromising their historical and cultural integrity.